Analysis of Teachers' and Students' Perceptions of Using Artificial Intelligence Chatbots in Higher Education - Subiyantoro, Singgih; Ekosusilo, Madyo; Ismail, Ismail; Putra, Hamda Kharisma; Fauziyah, Syifa (Cognitive Development Journal, 2023)
Artificial Intelligence (AI) chatbots have emerged as tools with the potential to enrich the learning experience. This research aims to analyze the perceptions of professors and students regarding the utilization of AI chatbots in the context of higher education. The primary objective of this study is to comprehend how teachers and students view the use of AI chatbots in higher education. This research adopts a qualitative approach employing semi-structured interviews and content analysis of relevant written documents. Data are collected and analyzed using descriptive statistics. The findings of this research reveal that most respondents, both professors and students, hold a positive attitude toward using AI chatbots in higher education. The critical benefits acknowledged include accessibility, assistance answering questions, and enhanced learning efficiency. Some challenges related to data security and the quality of interaction with chatbots are also identified. This research demonstrates that AI chatbots have significant potential to enhance the learning experience in higher education. However, attention must be given to existing technical challenges and privacy concerns to ensure broader acceptance. This study provides valuable insights into the perceptions of professors and students regarding AI chatbots, which can serve as a guide for educational institutions in developing effective implementation strategies. Furthermore, these results may stimulate further research into the use of AI technology in higher education.